Policy of notary deed in Indonesia, Netherland, and Belgium during the Covid-19 pandemic - Maghfira Humaira; Pieter Everhardus Latumeten (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study aims to compare the making of a notary deed during the Covid-19 period in Indonesia, the Netherlands and Belgium. Normative juridical law research is the method employed in this research. Analytical descriptive was further also utilized, while the data collection technique used is literature study. The results of the study indicated the importance of changes to Law Number 30 of 2004 concerning Notary Positions as amended by Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Positions ("Notary Position Law") in connection with by making an authentic deed which is carried out without physical presence, which facilitates Notaries to carry out their positions in times of emergency such as the current Covid-19 as the Netherlands and Belgium have fulfilled the element of legal expediency by enacting the Covid-19 Temporary Law ("Dutch Covid-19 Temporary Act") in the Netherlands. The Netherlands Covid-19 Temporary Act makes it possible to make a notarial deed without physical presence or to do it virtually. Meanwhile, in Belgium, a digital power of attorney has been implemented by The Royal Federation of Belgian Notaries and the Minister of Justice. The authors conclude that in Indonesia, the law regarding the position of a notary does not yet recognize virtual meetings but requires the making of a notary deed through parties who are directly related to a notary, while the Netherlands had previously implemented a rule that the making of a deed could be done using a two-way audiovisual communication facility for the prevention of COVID-19 and Belgium had implemented a digital power of attorney to make it easier for parties to use the service from a notary.